The Influence of Organizing Historical Textures on Citizenry Satisfaction in the Old Texture Neighbourhoods of Rasht - Reza Askarizad; Hossein Safari; Mohammadreza Pourimanparast (Emerging Science Journal, 2017)
Study about historical textures and its values is always one of the most important topics in recent decades of Iran. This research is based on organizing historical textures and its influence on citizenry satisfaction in the old texture neighbourhoods of Rasht. This case, start with recognition the neighbourhood and investigate of its problems and requirements of citizens who live there via codify questionnaire. In this research, it was attempted to organize historical textures, with cite descriptive - analytical method and base on field and library surveys. Also utilize SWOT model, in order to improve vitality situations with idealistic solutions in this historical texture. Results show that, this neighbourhood has physical & spatial weaknesses and it is not proportional with its resident’s requirements. In conclusion, according to investigates with organize historical textures in terms of physical, social, economic and environmental aspects, we're able to return dynamism, vivacity and vitality to the historical textures in addition to their requirements. Also preservation from historical textures, if done with tact and planning, it can create symbols of identity and culture for future generations.